Sensory and Motor Conduction Velocity in Spontaneously Hypertensive Rats: Sex and Aging Investigation - Fontanesi, Lucas B.; Fazan, Frederico S.; Dias, Fernando J.; Schiavoni, Maria Cristina L.; Marques Jr., Wilson; Fazan, Valéria Paula Sassoli (Frontiers in Systems Neuroscience, 2019)
The literature is extensive on how hypertension affects the morphology and function of the central nervous system and is being focused on multiple organ damage involving the kidneys, heart, endothelium and retina. Hypertension damage to the peripheral nervous system is less explored in the literature. We have previously showed morphometric alterations in large and small caliber myelinated fibers of nerves in the adult spontaneously hypertensive rat (SHR). However, the functional correlation of these findings has not been explored. We performed an electrophysiological investigation of hind limb nerves in SHR of both genders in different ages. Normotensive Wistar-Kyoto (WKY) rats were used as controls. Electrophysiological recordings and determination of motor (MCV) and sensory (SCV) nerve conduction velocity were performed in the same animals at 4 different ages: 5, 8, 20 and 40 weeks after birth. Comparisons were made between ages, genders and animals strain. We showed a continuous body weight increase in adult life in all animals studied. MCV got stable at 20 week old hypertensive animals and continued to increase in normotensive ones. The SCV was constant between ages of 20 and 40 weeks old in female SHR and decreased in male SHR while it continued to increase in WKY animals. The electrophysiological investigation of the nerves in WKY and SHR from both genders and different ages, associated with morphological and morphometric data from the literature suggest that hypertension affects the nerve function and might corroborate the development of a peripheral neuropathy.